A pioneer of Literary Aesthetics? : Humboldtian Writing in the Mirror of Modern Ecopoetics - Lenz, Markus Alexander (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
The article examines the extent to which Alexander von Humboldt can be regarded as a pioneer of modern ecopoetry. Humboldt combined scientific-empirical penetration with aesthetically sophisticated verbalization of ecosystems and human-nature relationships, creating unique and literarily refined depictions of nature. Humboldt’s writings show a deep connection with nature that goes beyond mere description, establishing an existential relationship with the world. His approach of aestheticizing nature without instrumentalizing it suggests an alternative both to the Cartesian separation of man and nature and to identitarian concepts of nature localization. Based on this assumption, the article discusses the significance of Humboldt’s work for modern ecopoetry.